EXPLORING THE EXPERIENCE OF EFL STUDENTS ENGAGED IN ASYNCHRONOUS E-LEARNING - Isabella Gloria Hariadi; Debora Chaterin Simanjuntak (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
Asynchronous e-learning is receiving growing attention because it encompasses learner-oriented approach which emphasizes on the development of learners' knowledge and skills. Henceforth it is imperative to explore students experience on asynchronous e-learning. This study aims to delineate the experience of senior high school students in learning English through asynchronous e-learning. This is a qualitative descriptive study in nature and the data collected were analysed using thematic analysis by incorporating interpretive description approach. The participants of study were senior high school students from Lemahwungkuk sub-district, Cirebon, Indonesia. The results revealed that in undergoing asynchronous e-learning, the participants have to implement self-access learning and additionally they have to adapt with technology setting which may appear to be challenging due to limited technical support they have; moreover they still have to discover the knowledge by themselves inasmuch as they experience limited interaction with their English teachers throughout the process of learning.